Al-Qaeda and sacrifice: martyrdom, war and politics - Finn, Melissa (Pluto Press, 2012)
Introduction 1 From the Vantage Point of Sacrificial Violence: Al-Qaeda's Worldview in Context 2 The Meanings of Sacrifice in Islam 3 Etymological Reflections on Sacrifice 4 Comparative Political Thought on War, Sacrifices, and Politics 5 The Limits of Sacrificial Subjectivity for Politics 6 Conclusion: Sacrificial Subjectivity for Acephalic Politics